Lesion evidence for a human mirror neuron system. (May 2017) - Binder, Ellen; Dovern, Anna; Hesse, Maike D.; Ebke, Markus; Karbe, Hans; Saliger, Jochen; Fink, Gereon R.; Weiss, Peter H.
Abstract: More than two decades ago, the mirror neuron system (MNS) was discovered in non-human primates: Single-cell recordings detected visuo-motor neurons that discharged not only when the monkey performed an action, but also when it observed conspecifics performing the same action. It has been proposed that a fronto-parietal circuitry constitutes the human homolog of the MNS. However, the functional role of a human MNS (i.e., whether it is functionally necessary for imitation or action understanding) to date remains controversial. We here examined how patients with left hemisphere (LH) stroke imitate, recognize, and comprehend intransitive meaningful limb actions. In particular, we investigated whether apraxic patients with lesions affecting key nodes of the putative human MNS show deficits in action imitation, action recognition, and action comprehension to a similar degree – as predicted by the MNS hypothesis. Behavioral results showed that patients with apraxia ( n  = 18) indeed performed significantly worse in all three motor cognitive tasks compared to non-apraxic patients ( n  = 26) and healthy controls ( n  = 19), whose performance did not differ significantly. Lesions of the apraxic (compared to non-apraxic) patients with LH stroke affected more frequently key regions of the putative human MNS, i.e., the left inferior frontal, superior temporal, and supramarginal gyri as well as the inferior parietal lobe ( p  < .01, false discovery rate – FDR-corrected). Albeit largely overlapping, voxel-based lesion-symptom mapping (VLSM) revealed that deficits in gesture comprehension were mainly associated with lesions of more anterior parts of the MNS, whereas lesions located more posteriorly mainly resulted in gesture imitation deficits ( p  < .05, FDR-corrected). Our clinical data support key hypotheses derived from the notion of a human MNS: LH lesions to the MNS core regions affected – critically and to a similar extent – the imitation, recognition, and comprehension of meaningful actions.